The Blessed Virgin Mary A Faithful Companion to God and Man. The Lucan Marian Perspective. PART TWO: The Blessed Virgin Mary as our Great Siste r - Zachary Ndegwa Kabatha (Studia Theologica Varsaviensia)
The term a great brother is in use today in many circles which captures the aspect of a faithful friend or companion. One who stands with the side that feels in adequate in one way or the other. This phenomenon is both manifested in the sacred as well as the secular realms of human existence. The inadequacy employed here refers to a wide range of being incapacitated. In our scope we will employ the term great sister instead of the great brother to refer to the Blessed Virgin Mary as our great sister. It is beyond doubt that our Blessed Mother stands tall in so many ways as compared to the modern man. It is in this line that Mary fits well not only to be called our companion but our great sister. Although the great brother may be understood in terms of political economical or even social power Mary has noble values than these ones. In this paper we propose to follow St Luke in his Marian presentation and offer her to all Christians today as our great sister. We refer to Mary as our great sister not out of her worldly power or wealth but simply because of her faith, holiness and commitment in her calling after she gave birth to our Saviour. As our great sister she stands with each of us in company of her Son with the sole intention of uplifting our lowly nature to the nature of her Divine Son. The presence of our blessed mother in our lives will seduce us with her heroic virtues which will be beneficial in our Christian life. To achieve our stated purpose in this article we shall articulate the role of the Blessed Virgin Mary in the event of presenting the child Jesus in the temple.